The Effect of Acumoxa Therapy on Blood Pressure in Gestational Hypertension - Ketut Anom Sri Kesumawati; Mardiyono Mardiyono; Leni Latifah (Alta Dharma Publisher, 2020)
Gestational hypertension (GH) adverse effects on pregnancy and fetal development, but there are still a few non-pharmacological interventions that can control blood pressure. The study aimed to examine the impact of acumoxa therapy on reducing blood pressure among patients with GH. Thirty-four patients were admitted to three community health centers in Brebes Regency. They were selected and randomly divided into two groups, such as the experimental group and the control group. This study's participation was pregnant women randomly allocated to the experimental group (n= 17) and control group (n=17). The intervention group received acumoxa therapy. The control group received acupressure therapy at the same time of 5 minutes at each point in 3 sessions per week for four weeks. The points used between the intervention and control groups were almost the same. Acupoints HT 7 and LI11 are given acumoxa and acupressure. Point GV20 is only covered by pressure, and point KI3 is only moxibustion. Of the 34 women who completed the study, those who received acumoxa had significantly lower mean arterial pressure (MAP) (mean difference = 8 mmHg, p<0.05). Acumoxa therapy is an effective non-pharmacological method for reducing blood pressure in patients with gestational hypertension